1980
DOI: 10.1073/pnas.77.10.5774
|View full text |Cite
|
Sign up to set email alerts
|

Structure of endogenous murine leukemia virus DNA in mouse genomes.

Abstract: By using molecularly cloned ecotropic AKR murine leukemia virus (MuLV) DNA, a 400 base-pair ecotropic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(132 citation statements)
references
References 29 publications
8
124
0
Order By: Relevance
“…B/W mice are known to produce a host of endogenous viruses. Although one of the parent strains, NZB, is thought to produce only nonecotropic virus, ecotropic MLV that is derived from the NZW strain (36) can be isolated from the B/W mouse (10,37). When injected with anti-CD4 antibody (38) or with CTLA4Ig (39), and thus prevented from succumbing to lupus disease, B/W mice develop B-cell leukemia.…”
Section: Accumulation Of 2-ltr Sequences From Endogenous MLV By Raltementioning
confidence: 99%
“…B/W mice are known to produce a host of endogenous viruses. Although one of the parent strains, NZB, is thought to produce only nonecotropic virus, ecotropic MLV that is derived from the NZW strain (36) can be isolated from the B/W mouse (10,37). When injected with anti-CD4 antibody (38) or with CTLA4Ig (39), and thus prevented from succumbing to lupus disease, B/W mice develop B-cell leukemia.…”
Section: Accumulation Of 2-ltr Sequences From Endogenous MLV By Raltementioning
confidence: 99%
“…(a) The restriction fragment map of the Lvis1 viral insertion site depicting the position and orientation (5' to 3') of the most frequently observed viral insertion in AKXD leukemias. Representative restriction maps of AKV ecotropic and MCF class II retroviruses (Chattopadhyay et al, 1980) are shown at the top of the ®gure. The shaded box below the map depicts the location of probe pL1.…”
Section: Gene Identi®cationmentioning
confidence: 99%
“…For T cell receptor ␤ chain (TCR␤) rearrangements, digestion was with HpaI and the probe was CT␤ (Hedrick et al, 1985). To screen for somatic integrations of ecotropic MuLV, DNAs were digested with EcoRI and occasionally PvuII and probed with the ecotropic-specific probe EcoSp, a 400-bp SmaI fragment (Chattopadhyay et al, 1980). For analysis of MCF MuLV genomes, an MCF-xenoSp probe (referred to as B-E in Chattopadhyay et al, 1982), which detects MCF and xenotropic MuLV sequences, was used.…”
Section: Molecular Studiesmentioning
confidence: 99%